Analysis of the Causes of Talking Disorders in the Elderly (Siti Rusani): Analisis Faktor Penyebab Gangguan Berbicara Latah Pada Lansia (Siti Rusani) - Faradilla Intan Sari (Perkumpulan Doktor Indonesia Maju (PDIM), 2020)
Talking is the act of parroting or imitating what other people are doing. However, talkative talk is actually a syndrome that is dirty and a provocable locomotor disorder. The words and sometimes accompanied by repetitive movements make the talkative teller look tormented by his condition. Talkative behavior does not only occur in children and adults but also in the elderly. Therefore, this research discusses factors that cause talkative speech disorders in the elderly. The purpose of this study is to describe or find out what are the factors that cause talkative disorders in the elderly. The research method used in this research is descriptive qualitative method and the data collection process is the method of observation, field notes, and documentation. The results of this study stated that Buk SR (Siti Rusani) had a disruption in talking talkative about caprolalia. This type of talkative sufferer will spontaneously say words that are considered taboo or obscene, which are usually their words concerning the male genitals.